Representasi Karakter Autism Spectrum Disorder dalam Drama Korea ‘Extraordinary Attorney Woo’ - Wijaya, Sherlina; Utami, Lusia Savitri Setyo (Koneksi, 2023)
The existence of public stigma against people with disabilities encourages writers to show disability issues in a literary work, namely drama. The Korean drama 'Extraordinary Attorney Woo' is one of the South Korean dramas that raises the issue of people with disabilities, autism spectrum disorder, through drama. By using Roland Barthes' semiotic analysis, researchers want to know and describe how the representation of autism spectrum disorder characters is displayed in the Korean drama 'Extraordinary Attorney Woo'. The theoretical foundations in this research are mass communication, drama, representation, autism spectrum disorder characters, and semiotics. This research is descriptive with a qualitative research approach. The results showed that the Korean drama 'Extraordinary Attorney Woo' is a form of mass communication that provides information by representing the life of a person with an autism spectrum disorder in South Korea. This is shown by the common stereotypes imposed on people with autism spectrum disorder and the lack of tolerance of society. In addition, there are difficulties in communicating, adapting, and interacting with people with autism spectrum disorder. The drama also shows the stigma and discrimination experienced by people with autism spectrum disorder in South Korea. Adanya stigma masyarakat terhadap penyandang disabilitas mendorong sastrawan untuk memperlihatkan isu disabilitas ke dalam sebuah karya sastra yaitu drama. Drama Korea ‘Extraordinary Attorney Woo’ merupakan salah satu drama Korea Selatan yang mengangkat isu penyandang  disabilitas, autism spectrum disorder, melalui drama. Dengan menggunakan analisis semiotika Roland Barthes, peneliti ingin mengetahui dan mendeskripsikan bagaimana representasi karakter autism spectrum disorder yang ditampilkan di dalam drama Korea ‘Extraordinary Attorney Woo’. Landasan teoritis dalam penelitian ini merupakan komunikasi massa, drama, representasi, karakter autism spectrum disorder, dan semiotika. Penelitian ini bersifat deskriptif dengan pendekatan penelitian kualitatif. Hasil penelitian menunjukkan, drama Korea ‘Extraordinary Attorney Woo’ merupakan salah satu bentuk komunikasi massa yang memberikan informasi dengan merepresentasikan kehidupan seorang penyandang autism spectrum disorder di Korea Selatan. Hal ini ditunjukkan dengan stereotip umum yang dikenakan pada penyandang dan kurangnya toleransi masyarakat. Selain itu, terdapat kesulitan berkomunikasi, beradaptasi, dan berinteraksi penyandang autism spectrum disorder. Drama juga menunjukkan stigma buruk hingga diskriminasi yang dialami oleh penyandang autism spectrum disorder di Korea Selatan.